Preliminary Study of Mangrove Eco-Structures and Natural Regeneration at Gili Lawang, East Lombok, West Nusa Tenggara) - Niechi Valentino; Andrie Ridzki Prasetyo; Muhammad Anwar Hadi (Jurnal Penelitian Pendidikan IPA, 2023)
Gili Lawang mangroves as a unique ecosystem, unstable, dynamic and complex. The purpose of this study is to determine the eco-structure and natural regeneration of the Gili Lawang mangroves as an initial study in sustainable mangrove forest management. This study used a systematic sampling method with random start, at 6 stations with a total of 60 plots. Seven types of mangroves were obtained, namely A. marina, B. cylindrica, B. gymnorrhiza, R. apiculata, R. mucronata, R. stylosa, and S. alba at the study site. The highest IVI was R. mucronata with a value of 79.34% (seedlings), B. gymnorrhiza with an IVI of 77% (saplings) and tree stage (96.2%). Canopy stratification is type C, D and E. The concentration of horizontal structures is in class 1 (10-16 cm). At the seedling growth stage H' was classified as moderate (1.33), E' was moderate (0.69), and R1 was low (1.13). At the stake level H' classified as Moderate (1.31), E' is moderate (0.67) and R1 is low (1.04) and at the tree level H' is classified as moderate (1.59), E' is high (0.82), R1 is low (0.95). The distribution of mangrove species in Gili Lawang was normally distributed with a distribution pattern of plant species generally clustered, except for S. alba at the sapling growth stage which were scattered randomly. The regeneration status of mangrove species in Gili Lawang is good in speciesA. marina, B. gymnorrhiza, R. apiculata,and R. mucronata, and sufficient/moderate on B. cylindrica, R. stylosa and S. alba.